Working Capital and Corporate Performance : Empirical Evidence from Three Manufacturing Industries - Niemi, Sofia (My University, 2023)
This master’s thesis aims to investigate the optimal working capital level for the manufacturing industry in the mining, quarrying, and construction segment between 2013-2021. The sample includes all geographical regions. In addition, the thesis tries to find a benchmark for the multinational company in this industry. The availability of cash is also included in the study because it is essential part in investing in working capital. The study uses fixed-effect panel analysis to investigate the relationship between working capital and corporate profitability. The sample includes 809 observations. Return on assets (ROA) measures profitability, while cash conversion cycle (CCC) measures working capital management. The control variables are size, leverage, and growth. Cash flow and cash holding measurements evaluate the availability of cash flow. The results show a convex relationship between working capital and profitability. On average companies should adopt aggressive working capital management. This action aims to shorter the CCC, and specifically DIO and DSO. DIO and DSO have the most significant impact on profitability, and the firms should focus on shortening these two components to achieve superior profitability.

Tämän pro gradu -tutkielman tavoitteena on selvittää optimaalista käyttöpääomatasoa kaivos-, louhinta- ja rakennussegmentissä vuosina 2013-2021. Otos sisältää kaikki maantieteelliset alueet. Lisäksi opinnäytetyössä pyritään löytämään vertailukohta alan monikansalliselle yritykselle. Myös käteisen saatavuus sisältyy tutkimukseen, koska se on olennainen osa käyttöpääomaan sijoittamisessa. Tutkimuksessa käytetään paneelianalyysiä käyttöpääoman ja yrityksen kannattavuuden välisen suhteen tutkimiseen. Otos sisältää noin 809 havaintoa. Tutkimuksessa ROA mittaa kannattavuutta, kun taas CCC mittaa käyttöpääoman hallintaa. Ohjausmuuttujat ovat koko, vipuvaikutus ja kasvu. Kassavirran ja kassavarojen muuttujat testaavat kassavirran saatavuutta. Tulokset osoittavat kuperan suhteen käyttöpääoman ja kannattavuuden välillä. Toisin sanoen yritysten tulisi omaksua aggressiivinen käyttöpääoman hallinta. Tällä toimella pyritään lyhentämään käyttöpääomasykliä ja erityisesti varastonkiertoa ja myyntisaamisia. Varastonkierolla ja myyntisaamisella on merkittävin vaikutus kannattavuuteen, ja yritysten tulisi keskittyä näiden kahden komponentin lyhentämiseen erinomaisen kannattavuuden saavuttamiseksi.
Keywords: profitability; working capital; cash flow; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance